Respon Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) terhadap Pemberian Pupuk Silika pada Kondisi Lengas Tanah yang Berbeda - Wideratih, Anggun Angling; Nurrachman, Nurrachman; Jufri, Afifah Farida (Universitas Muhammadiyah Mataram, 2025)
This research aims to examine the effect of Silica fertilizer on cayenne pepper (Capsicum frutescens) under water stress conditions on the growth and yield of chili plants. The study was designed with a 2-factor treatment arranged in a completely randomized design (CRD). The treatments tested were the effects of various concentration of Silica fertilizer (0 ml/l, 2 ml/l, and 4 ml/l) under different soil moisture conditions (80%, 100%, and 120% field capacity). The parameters observed included plant height, canopy width, stem diameter, number of productive branches, number of flowers, number of fruits per plant, and fruit weight per plant. The results showed that the use of Silica fertilizer at different concentration under water stress conditions had no significant effect on growth parameters such as plant height, canopy width, and stem diameter. However, the application of 4 ml/l Silica fertilizer resulted in better outcomes compared to plants with no Silica or 2 ml/l Silica in terms of yield parameters, such as fruit set percentage, number of harvested fruits, and fruit weight. The best interaction between Silica fertilizer treatment and water stress conditions was found in the S2KL1 treatment (4 ml/l Silica, 80% field capacity) and S2KL2 treatment (4 ml/l Silica, 100% field capacity).